2009
DOI: 10.1001/archdermatol.2009.169
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Café au Lait Macules at Initial Consultation in the Diagnosis of Neurofibromatosis Type 1

Abstract: To evaluate the predictive utility of the number and morphologic appearance of isolated café au lait macules (CALMs) in establishing the diagnosis of neurofibromatosis type 1 (NF1) in a cohort of children referred to an NF1 subspecialty clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 20 publications
3
49
0
3
Order By: Relevance
“…CLS is well established as the first NF1 diagnosis criterion, and its positive predictive value has been reported by several authors [5,19]. In a prospective 2-year program of clinical examination, 75% of 41 children with 6 or more typical CLS and no other sign or family NF1 history presented the NF1 phenotype by the age of 6 years, with 2 or more NF1 diagnosis criteria [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLS is well established as the first NF1 diagnosis criterion, and its positive predictive value has been reported by several authors [5,19]. In a prospective 2-year program of clinical examination, 75% of 41 children with 6 or more typical CLS and no other sign or family NF1 history presented the NF1 phenotype by the age of 6 years, with 2 or more NF1 diagnosis criteria [20].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the predictive value of 6 or more isolated CLS was reported in a cohort of 110 children. In this study, children met NF1 criteria in 76% by the age of 4 years, 96% by the age of 6 years and all by the age of 8 years [19]. …”
Section: Discussionmentioning
confidence: 99%
“…La neurofibromatose de type 1 de von Recklinghausen est la plus fréquente des phacomatoses (1/3500). La présence d'au moins 6 taches cutanées café au lait en est très évocatrice [13]. Cette maladie génétique à transmission autosomique dominante est associée à une fréquence élevée de phéochromocytome [14].…”
Section: La Discussionunclassified
“…Hence one can vehemently conclude that observance of occasional pigmentation may be the only clue to accurate diagnosis and appropriate treatment in such child patient with no other obvious manifestation of this disease. [8,9] Johnson et al reported more 3,4-dihydroxyphenylalanine (DOPA) positive melanocytes in CALS of NF1 patients than the surrounding skin. Also, these melanocytes contained giant pigmented granules.…”
Section: Discussionmentioning
confidence: 99%